2022
DOI: 10.1371/journal.pone.0264182
|View full text |Cite
|
Sign up to set email alerts
|

Is body fat mass associated with worse gross motor skills in preschoolers? An exploratory study

Abstract: We compared the motor competence between overweight/obese and eutrophic preschoolers with similar physical activity levels, age, socioeconomic status, maternal education, quality of the home environment and quality of the school environment. We also investigated to what extent excess body fat mass explains gross motor skills in preschoolers. A cross-sectional quantitative and exploratory study was conducted with 48 preschoolers assigned into eutrophic and overweight/obese groups. Overweight/obese preschoolers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Nevertheless, in investigations that analyzed age groups similar to those of the present study, positive associations were found between children's performance and mother's education level, as well as a greater probability of children who studied in schools with lower socioeconomic levels to have lower MC in tasks involving balance, agility and coordination, when compared to children with higher socioeconomic status (Tsapakidou et al, 2014). In the present study, the mothers' education level and the type of school showed no association with GMC assessed by KTK, which was also recently observed in the literature (Nobre et al, 2022). In view of this, even explaining only 24.2% of the variance in KTK performance, the data from the present study confirm that excess body weight negatively influences the performance of prepubertal children in KTK, regardless of the mother's education level and type of the child's school.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nevertheless, in investigations that analyzed age groups similar to those of the present study, positive associations were found between children's performance and mother's education level, as well as a greater probability of children who studied in schools with lower socioeconomic levels to have lower MC in tasks involving balance, agility and coordination, when compared to children with higher socioeconomic status (Tsapakidou et al, 2014). In the present study, the mothers' education level and the type of school showed no association with GMC assessed by KTK, which was also recently observed in the literature (Nobre et al, 2022). In view of this, even explaining only 24.2% of the variance in KTK performance, the data from the present study confirm that excess body weight negatively influences the performance of prepubertal children in KTK, regardless of the mother's education level and type of the child's school.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, studies that attempted to establish such relationships presented inconsistent data, but pointed to a positive association between socioeconomic status and locomotor and stability skills (Barnett et al, 2016). However, other studies have identified that socioeconomic status explains a minor part of the performance in motor coordination tests or is not significant, and that maternal education level does not seem to explain the motor performance of children in early childhood (Kakebeeke et al, 2021;Nobre et al, 2022). Nevertheless, in investigations that analyzed age groups similar to those of the present study, positive associations were found between children's performance and mother's education level, as well as a greater probability of children who studied in schools with lower socioeconomic levels to have lower MC in tasks involving balance, agility and coordination, when compared to children with higher socioeconomic status (Tsapakidou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported an association between locomotor proficiency and BMI in typically developing children ( 59 ); (Ramirez, Pérez-Cañaveras Herrero, 2021); ( 60 , 61 , 62 , 63 , 64 ). However, the extensive literature evidence indicates the BMI effect in LOCS ( 65 , 66 , 61 , 64 ) or a significant but non-directional relationship (i.e., correlation) ( 62 ); ( 67 ) ( 68 ); between these variables. Few studies have investigated the effect of locomotor skills on BMI ( 59 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overweight or excess body fat has been found to increase the risk of both poor motor skills [ 38 ] and spinal pain, also in children [ 39 ], and therefore, height and weight at baseline were also included as potential confounders.…”
Section: Methodsmentioning
confidence: 99%